Tuning the Kingdom : Kawuugulu Musical Performance, Politics, and Storytelling in Buganda - Kafumbe, Damascus (Book collections on Project MUSE., 2018)
Tuning the Kingdom draws on oral and written accounts, archival research, and musical analysis to examine how the Kawuugulu Clan-Royal Musical Ensemble of the Kingdom of Buganda (arguably the kingdom's oldest and longest-surviving performance ensemble) has historically managed, structured, modeled, and legitimized power relations among the Baganda people of south-central Uganda. Damascus Kafumbe argues that the ensemble sustains a complex sociopolitical hierarchy, interweaving and maintaining a delicate balance between kin and clan ties and royal prerogatives through musical performance and storytelling that integrates human and nonhuman stories. He describes this phenomenon as "tuning the kingdom," and he compares it to the process of tensioning or stretching Kiganda drums, which are always moving in and out of tune. Even as Kawuugulu continues to adapt to the rapidly changing world around it, Tuning the Kingdom documents how Kawuugulu has historically articulated and embodied principles of the three inextricably related domains that serve as the backbone of Kiganda politics: kinship, clanship, and kingship."